Thematic mapping of artificial intelligence in management: A bibliometric approach using co-word analysis (2015–2024) - Salgado-García, Jorge Arturo; Terán-Bustamante, Antonia; Velázquez-Salazar, Marisol (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. The objective of this study was twofold: first, to map the main themes in the literature on artificial intelligence in management, and second, to explore the relationships between these themes. Design/Methodology/Approach. A co-word analysis was performed on 15,835 articles indexed in Scopus (2015–2024), with the author’s keywords in the field of administration constituting the unit of analysis. The semantic network under consideration was constructed using the 50 most frequent terms, applying normalization by association and the Walktrap algorithm for cluster detection. Results/Discussion. The results of the analysis indicated that the extant literature was organized around three thematic groups. The first of these focused on conversational interfaces, the second on digital transformation, and the third adopted a computational approach. The thematic structure identified reflected a field in the process of consolidation, with a predominance of technical approaches and limited functional specialization. Conclusion. Contemporary research endeavors prioritized methodological development over strategic implementation in particular organizational contexts. These findings underscored the necessity for more comprehensive approaches that articulated technology, management, and governance. Moreover, they called for a future agenda that was oriented toward its adoption from sociotechnical perspectives.